Multi-Omics Insights into Regulatory Mechanisms Underlying Differential Deposition of Intramuscular and Abdominal Fat in Chickens - Yuxin Xing; Chenglin Ma; Hongbo Guan; Jianing Shen; Ying Shen; Guoxi Li; Guirong Sun; Yadong Tian; Xiangtao Kang; Xiaojun Liu; Hong Li; Weihua Tian (Biomolecules)
Excessive abdominal fat deposition in chickens disadvantages feed conversion, meat production, and reproductive performance. Intramuscular fat contributes to meat texture, tenderness, and flavor, serving as a vital indicator of overall meat quality. Therefore, a comprehensive analysis of the regulatory mechanisms governing differential deposition of abdominal versus intramuscular fat is essential in breeding higher-quality chickens with ideal fat distribution. This review systematically summarizes the regulatory mechanisms underlying intramuscular and abdominal fat traits at chromatin, genomic, transcriptional, post-transcriptional, translational, and epigenetic-modification scales. Additionally, we summarize the role of non-coding RNAs and protein-coding genes in governing intramuscular and abdominal fat deposition. These insights provide a valuable theoretical foundation for the genetic engineering of high-quality and high-yielding chicken breeds.